The impact of the Covid-19 pandemic and various lockdown levels on emergency medical services response times to trauma incidents in the Western Cape Province, South Africa - Alrashed, Omar (Division of Emergency Medicine, 2025)
The outbreak of the COVID-19 crisis presented an immense challenge to both private and public health institutions and brought to the fore the importance of emergency medical services. The COVID-19 crisis provided evidence of the importance of out-of-hospital care for the lives of the patients depending on access to prompt medical care. Emergency Medical Services (EMS) serve as the first step in accessing the healthcare system for many within South Africa and as such played a pivotal role in the continuation of initiating medical care during the COVID-19 pandemic. The importance of EMS within the healthcare system was highlighted during the pandemic due to increased pressures placed on an already overstrained healthcare system.